Irish building workers, 1943 (1943)
1943 1939-1945 "Irish building workers, 1943" [hfr0195], 1943 These articles relating to discrimination against building workers from Ireland are from the 'New Builders Leader and Electricians Journal' October 1943. From early 1940 to mid-1945, 60,000 workers were transferred from Northern Ireland to Great Britain. There are no complete records for the net number of Eire workers recruited during the war, but between 1941 -1945 almost 100,000 travelled from Eire to GB for work. Most men were recruited into agriculture or building and most women into nursing, cleaning and related work